Course of helminthic gastrintestinal infection in calves - Leite, Antonio Cesar Rios; Guimarães, Marcos Pezzi; Costa, José Oswaldo; Costa, Helio Martins de Araujo; Lima, Walter dos Santos (Pesquisa Agropecuaria Brasileira, 2014)
Worm free calves were put in the pasture in the begining (20 animals) and in the and (20 animals) of the rainy season and in the middle of the dry season (20 animals). Two animals were necropsied monthly in order to count and identify the helminths. The animals put in the pasture in the begining of the rainy season were more heavily infected with gastrintestinal nematodes than those put in the end of the rainy season and in the dry season (P<0.05). The helminths found at necropsy of the animals were Cooparia punctata, Haemonchus contortus, H. similis, Trichostrongylus axei, Oesophagostomum radiatum, Bunostomum phlebotomum and Trichuris discolor. No statistical difference in weight gain was found among the animals of the three groups.